Shipwrecks and Qingbai Porcelain Trade during Song and Yuan Dynasties, China - Xue, Xiyan (2022)
Qingbai porcelain was a major commodity in overseas trade during the period of Song and Yuan dynasties, but the current research on export Qingbai wares is much less than that on celadon and blue and white porcelain. In recent years, considerable archaeological discoveries of shipwrecks carrying Qingbai porcelain, make it possible for a further study of export Qingbai porcelain and its maritime trade.